Analysis of an unprecedented sting jet storm over central Europe based on high-resolution ICON-LAM simulations - Eisenstein, Lea; Pantillon, Florian; Knippertz, Peter; Pinto, Joaquim G. (2023)
Cyclonic windstorms belong to the most destructive natural hazards over Europe. Heavy wind gusts in cyclones are often associated with the cold and warm conveyor belts, as well as frontal convection. In recent years, another wind phenomenon, the so-called sting jet, has been discussed accompanying Shapiro-Keyser cyclones. This is an air stream which descends from the cloud head in the mid-troposphere into the frontal-fracture region of the cyclone and causes strong near-surface gusts. Although the sting jet can merge with the cold conveyor belt jet at some point of evolution of the cyclone, it is distinct from other low-level jets. The question of what mechanisms cause or contribute the descending are not fully understood yet. Suggested processes include mesoscale instabilities and frontal dynamics. Furthermore, the literature is almost entirely focused on Sting Jet case studies over the North Atlantic, the British Isles, and the North Sea. This work focuses on windstorm Egon (12-13 January 2017) a case study with an apparent Sting Jet over France and Germany, thus unprecedented over continental Europe. To analyse the storm, ICON in limited area mode is used for simulations with horizontal grid spacings down to 1.6 km and different vertical resolutions. With such a fine grid spacing the orography is well represented and convection is explicitely resolved. Lagrangian trajectories calculated with LAGRANTO confirm the presence of a descending air stream in the cyclone and thus of a sting jet. They further show consistency with most of the widely accepted characteristics of sting jets, namely descent on surfaces of constant wet-bulb potential temperature and acceleration during the descent, while no consistency is found in values of relative humidity, which do not show the expected drying out. Furthermore, a possible contribution of conditional symmetric instability and evaporative cooling is detected, two processes suggested by previous studies. Since this case is the first reported sting jet storm over continental ...